Accounting for Oil and Gas Producing Companies, Part 1: Exploration, Acquisition, Development, and Production (Book). - Meyer, Philip E.; Myers, John H. (The Accounting Review, 1982)
Abstract Reviews the book "Accounting for Oil and Gas Producing Companies," Part 1, "Exploration, Acquisition, Development, and Production," by Horace R. Brock, John P. Kungstedt. and Donald M. Jones.